Does the locus on chromosome 11 implicated in susceptibility to HLA-DR4 dependent type I diabetes mellitus also affect susceptibility to rheumatoid arthritis?. Issue 11 (November 1992) - Pile, K D; Wordsworth, B P; Bell, J I
Abstract : There is a polygenic component to rheumatoid arthritis (RA) in addition to the known association with HLA-DR4. It has previously been shown in another autoimmune disease (type I diabetes mellitus) that a gene on chromosome 11p can act with HLA-DR4 to enhance susceptibility (relative risk 5-6). It is therefore possible that this locus may also affect the development of RA. Genotype frequencies at this locus, defined by a dimorphic Fok 1 restriction site, were compared in 139 healthy controls and 213 patients with classical/definite RA. In contrast with diabetes there was no increase in genotypes lacking the Fok 1 site, either in the rheumatoid group overall (125/211 compared with 86/139 controls) or in the DR4 positive rheumatoid group (76/140 compared with controls). These results indicate that the interaction between DR4 and a locus on chromosome 11p is not common to all DR4 associated autoimmune diseases.